Proactive Community Occupational Therapy Service for Social Participation Development of Thai Adults with Depression: A Grounded Theory Study from Occupational Therapists' Perspective - Supaluck Phadsri; Rieko Shioji; Atsuko Tanimura; Sopida Apichai; Jeerawit Jaknissai (Hindawi-Wiley, 2021)
Introduction. Depression in adulthood decreases social participation in the workplace, family, and community, which further results in decreased work performance and cessation and social isolation. There is a high statistic of outpatient consultation and readmission of Thais with depression, yet the mental health support for remission in community life and social participation remains limited and unclear. Further, due to the lack of mental health professional resources, particularly occupational therapists, there is much to be known regarding how such therapists work to support the development of social participation in Thai adults with depression. Objective. This research was aimed at understanding the process of how occupational therapists work to redevelop the social participation of community-dwelling Thai adults with depression. Method. The grounded theory methodology was used in this study. Data were collected through interviews and nonparticipatory observations of 14 participants who had experience providing mental health care in community services. The constant comparative analysis method was employed. Result. Three concepts illustrated a proactive community occupational therapy service for depression (PCOTS-D), namely, integrating depression care in community occupational therapy service (COTS), supporting meaningful participation, and forming collaborative networks. The PCOTS-D supported the reconnection of social participation by leading from proactive depression care service to COTS and then working to support meaningful participation toward the patient's self-management and building collaborative networks with inter- and intraprofessional teams simultaneously. Conclusion. The PCOTS-D presented a holistic view of working with community-dwelling Thai adults with depression by considering the importance of the community and researchers' network to redevelop social participation, promote health and recovery, build teams in depression care, and encourage research evidence to enhance the supportive advocacy policy for Thai people with depression.